A 560 yr summer temperature reconstruction for the Western Mediterranean basin based on stable carbon isotopes from Pinus nigra ssp. laricio (Corsica/France). - Szymczak, Sonja; Joachimski, Michael; Bräuning, Achim; Hetzer, Timo; Kuhlemann, Joachim (Climate of the Past, 2012)
The Mediterranean is considered as an area which will be affected strongly by current climate change. However, temperature records for the past centuries which can contribute to a better understanding of future climate changes are still sparse for this region. Carbon isotope chronologies from tree-rings often mirror temperature history but their application as climate proxies is difficult due to the influence of the anthropogenic change in atmospheric CO2 on the carbon isotope fractionation during photosynthetic CO2 uptake. We tested the influence of different correction models accounting for plant response to increased atmospheric CO2 on four annually resolved long-term carbon isotope records (between 400 and 800 yr) derived from Corsican pine trees (Pinus nigra ssp. laricio) growing at ecologically varying mountain sites on the island of Corsica. The different correction factors have only a minor influence on the main climate signals and resulting temperature reconstructions. Carbon isotope series show strong correlations with summer temperature and precipitation. A summer temperature reconstruction (1448–2007 AD) reveals that the Little Ice Age was characterised by low, but not extremely low temperatures on Corsica. Temperatures have been to modern temperatures at around 1500 AD. The reconstruction reveals warm summers during 1480–1520 and 1950–2007 AD and cool summers during 1580–1620 and 1820–1890 AD.
UnivIS-Import:2015-03-09:Pub.2012.nat.dgeo.IGM.LG.a560yr

Are pooled tree ring δ13C and δ18O series reliable climate archives? — A case study of Pinus nigra spp. laricio (Corsica/France). - Szymczak, Sonja; Joachimski, Michael; Bräuning, Achim; Hetzer, Timo; Kuhlemann, Joachim (Chemical Geology, 2012)
Stable carbon and oxygen isotopes in tree rings are considered as reliable climate archives as they provide past environmental information with high resolution. However, recent studies have shown that isotope chronologies may reveal a long-term age trend and be influenced by non-climatic factors as other tree-ring parameters as well. These trends can only be identified in chronologies measured on individual trees but not on pooled sample chronologies consisting of several trees. In order to test whether pooled chronologies from pine trees from the Island of Corsica (Mediterranean/France) can be used for climatic reconstructions, we compared calculated mean values from 5 individual trees with pooled chronologies from the same 5 individuals. Carbon and oxygen isotope chronologies for a 50-year interval with annual resolution and 400 years with decadal resolution were analysed in order to document secular changes in inter-tree variability and to test for age related trends in the isotope ratios. Pooled carbon and oxygen isotope series correspond well to chronologies based on mean values calculated from analyses of individual trees. Inter-tree variability in oxygen isotope ratios is higher than in carbon isotope ratios but remains relatively constant over time. Similarities between the isotope series of individual trees are stronger over the 400-year time scale documenting a common long-term signal in the isotope values. No long-term age related trends are observed. Oxygen isotope values of the juvenile phase are characterised by a remarkable decrease over 40–50 years, interpreted to be related to the less developed root system of the young trees. This age effect can be avoided by not considering the first 50 years from the chronologies. Our results confirm that pooled carbon and oxygen isotope chronologies from Pinus nigra can be used for environmental reconstructions without statistical detrending.
UnivIS-Import:2015-03-09:Pub.2012.nat.dgeo.IGM.LG.arepoo
Keywords: Tree rings; Carbon isotopes; Oxygen isotopes; Pooling; Age trend; Pinus nigra ssp. laricio

Combining wood anatomy and stable isotope variations in a 600-year multi-parameter climate reconstruction from Corsican black pine - Szymczak, Sonja; Hetzer, Timo; Bräuning, Achim; Joachimski, Michael; Leuschner, Hanns-Hubert; Kuhlemann, Joachim (Quaternary Science Reviews, 2014)
We present a new multi-parameter dataset from Corsican black pine growing on the island of Corsica in the Western Mediterranean basin covering the period AD 1410-2008. Wood parameters measured include tree-ring width, latewood width, earlywood width, cell lumen area, cell width, cell wall thickness, modelled wood density, as well as stable carbon and oxygen isotopes. We evaluated the relationships between different parameters and determined the value of the dataset for climate reconstructions. Correlation analyses revealed that carbon isotope ratios are influenced by cell parameters determining cell size, whereas oxygen isotope ratios are influenced by cell parameters determining the amount of transportable water in the xylem. A summer (June to August) precipitation reconstruction dating back to AD 1185 was established based on tree-ring width. No long-term trends or pronounced periods with extreme high/low precipitation are recorded in our reconstruction, indicating relatively stable moisture conditions over the entire time period. By comparing the precipitation reconstruction with a summer temperature reconstruction derived from the carbon isotope chronologies, we identified summers with extreme climate conditions, i.e. warm-dry, warm-wet, cold-dry and cold-wet. Extreme climate conditions during summer months were found to influence cell parameter characteristics. Cold-wet summers promote the production of broad latewood composed of wide and thin-walled tracheids, while warm-wet summers promote the production of latewood with small thick-walled cells. The presented dataset emphasizes the potential of multi-parameter wood analysis from one tree species over long time scales. © 2014 Elsevier Ltd.
UnivIS-Import:2015-04-14:Pub.2014.nat.dgeo.IGM.LG.combin
Keywords: Carbon isotopes; Climate reconstruction; Mediterranean; Oxygen isotopes; Pinus nigra; Tree ring anatomy

High-resolution climatic analysis of wood anatomical features in Corsican pine from Corsica (France) using latewood tracheid profiles - Hetzer, Timo; Bräuning, Achim; Leuschner, Hanns-Hubert (Trees-Structure and Function, 2014)
Abstract: We analyzed latewood anatomical features from Corsican pine (Pinus nigra ssp. laricio) of high-elevation sites in Corsica (France) derived from digital images of the wood surface. Latewood of each ring during the period 1950–2008 was partitioned into ten equal parts P1–P10. Mean values of the cell parameters cell lumen area (CLA), radial cell width (RCW), radial cell wall thickness (CWT), and modeled latewood density (MLD) were calculated for P1–P10. The cellular profiles for each cell parameter were subjected to principal component analyses. It was possible to quantify macroscopically visible variations of wood anatomy like intra-annual density fluctuations (IADFs) by latewood profiles of different cell parameters. A combination of cell parameter characteristics including their relative radial position within latewood provides a quantification of the cell anatomical variations in an IADF. Individual cell parameter chronologies and principal components of cell parameter profiles were correlated with climate data to determine the climatic forcing on latewood formation. Average cell parameter profiles and deviations from the long-term means are able to describe “normal” and “anomalous” environmental conditions during latewood formation. Cell feature anomalies throughout the latewood during individual years allow the reconstruction of past weather conditions with a high temporal resolution.
Keywords: Dendroecology; France; Mediterranean climate; Pinus nigra; Wood anatomy; Wood cell parameters